2009
DOI: 10.1056/nejmoa0902905
|View full text |Cite
|
Sign up to set email alerts
|

On-Pump versus Off-Pump Coronary-Artery Bypass Surgery

Abstract: At 1 year of follow-up, patients in the off-pump group had worse composite outcomes and poorer graft patency than did patients in the on-pump group. No significant differences between the techniques were found in neuropsychological outcomes or use of major resources. (ClinicalTrials.gov number, NCT00032630.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
591
11
28

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,023 publications
(654 citation statements)
references
References 31 publications
24
591
11
28
Order By: Relevance
“…Although a recent prospective randomized trial identified OPCAB to have no advantage in low-risk patients [16], it appears to be the superior method of revascularization in high-risk patients [9,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent prospective randomized trial identified OPCAB to have no advantage in low-risk patients [16], it appears to be the superior method of revascularization in high-risk patients [9,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In CORONARY,27 the primary composite outcome of death, nonfatal stroke, or nonfatal myocardial infarction (MI) was similar between OPCAB and ONCAB (9.8% versus 10.3%, P =0.59). Similarly in ROOBY, the primary composite outcome of 30‐day death or major complications was similar between the 2 arms (7.0% versus 5.6%, P =0.19) 38. Furthermore, there was no difference in any individual component of these early composite outcomes (Table 1).…”
Section: Comparison Of Short‐term Clinical Outcomes Of On‐ and Off‐pumentioning
confidence: 80%
“…In the largest randomized comparisons (CORONARY [CABG Off or On Pump Revascularization] and ROOBY [Randomized On/Off Bypass] trials), there were no differences in the primary study end point at 30 days 27, 38. In CORONARY,27 the primary composite outcome of death, nonfatal stroke, or nonfatal myocardial infarction (MI) was similar between OPCAB and ONCAB (9.8% versus 10.3%, P =0.59).…”
Section: Comparison Of Short‐term Clinical Outcomes Of On‐ and Off‐pumentioning
confidence: 99%
“…Наибо-лее информативные рандомизированные исследования включали как пациентов с относительно невысоким риском вмешательства (ROOBY), так и больных стар-ше 75 лет со значительно худшими характеристиками (GOPCABE). Эти исследования, как и большинство ме-таанализов, продемонстрировали, что ранние и годич-ные результаты КШ off-pump сравнимы с результатами стандартных операций, однако в группах off-pump от-мечена большая неполная реваскуляризация, необхо-димость повторных вмешательств и худшая проходи-мость шунтов [44,45]. Недавно опубликованная работа B.H.…”
Section: тактика операцииunclassified